Faktor-Faktor yang Mempengaruhi Risiko Sistematis Saham dengan Good Corporate Governance Sebagai Variabel Moderasi - Veni Vionita; Suwarno Suwarno (Universitas Muhammadiyah Gresik, 2022)
This study aims to examine the factors that influence the systematic risk of stocks with good corporate governance as a moderating variable in LQ45 companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This study uses quantitative methods with secondary data in the form of complete company financial statements. The research sample amounted to 19 LQ45 companies which were analyzed using purposive sampling technique. The analysis method uses Partial Least Square (PLS) analysis, with the help of WarpPLS 7.0 software. The results show that liquidity has a positive and significant effect on stock systematic risk, leverage has a negative and insignificant effect on stock systematic risk, profitability has a negative and significant effect on stock systematic risk, growth has a negative and significant effect on stock systematic risk, good corporate governance is not able to moderate the effect of liquidity, leverage, profitability, growth on stock systematic risk.